80 years later: Marine sediments still influenced by an old war ship - Van Landuyt, Josefien; Kundu, Kankana; Van Haelst, Sven; Neyts, Marijke; Parmentier, Koen; De Rijcke, Maarten; Boon, Nico (Frontiers in Marine Science, 2022)
Historic shipwrecks form an anthropogenic landmark in marine environment, yet their influence on the local geochemistry and microbiology remains largely unexplored. In this study, sediment and steel hull samples were taken around the V-130 John Mahn, a World War II shipwreck, at increasing distance from the wreck, in different directions. Polycyclic aromatic hydrocarbons (PAH), explosives, and heavy metal levels were determined and related to the microbial composition. Benz(a)anthracene and fluoranthene remain present at the mg kg-1 level, probably originating from the coal bunker. This indicates that the wreck is still influencing the surrounding sediments. Known PAH degrading taxa like Rhodobacteraceae and Chromatiaceae were more abundant in samples with high aromatic pollutant content. Moreover, sulphate reducing bacteria (such as Desulfobulbia) are taking part in the corrosion of the steel hull. This study shows that even after 80 years, a historic shipwreck can still significantly steer the surrounding sediment chemistry and microbial ecology.